2021
DOI: 10.1007/s00146-021-01303-z
|View full text |Cite
|
Sign up to set email alerts
|

On and beyond artifacts in moral relations: accounting for power and violence in Coeckelbergh’s social relationism

Abstract: The ubiquity of technology in our lives and its culmination in artificial intelligence raises questions about its role in our moral considerations. In this paper, we address a moral concern in relation to technological systems given their deep integration in our lives. Coeckelbergh develops a social-relational account, suggesting that it can point us toward a dynamic, historicised evaluation of moral concern. While agreeing with Coeckelbergh’s move away from grounding moral concern in the ontological propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Secondly, my analysis of their case-by-case method demonstrated that the Relationist can neither secure objective morality nor provide sufficient action guidance. Despite considering Gunkel's ethical pluralism (2018a) I, following Tollon and Naidoo (2021) and Mosakas (2020), concluded that this is not a satisfactory response. Thus, this essay has illustrated that not only is the Relationist's method of ascribing AMS anthropocentric, it cannot secure sufficient action guidance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, my analysis of their case-by-case method demonstrated that the Relationist can neither secure objective morality nor provide sufficient action guidance. Despite considering Gunkel's ethical pluralism (2018a) I, following Tollon and Naidoo (2021) and Mosakas (2020), concluded that this is not a satisfactory response. Thus, this essay has illustrated that not only is the Relationist's method of ascribing AMS anthropocentric, it cannot secure sufficient action guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Following Tollon and Naidoo (2021), this issue pertains to the Relationist's fundamental caseby-case method of ascription as, as individuals "we often misinterpret the moral nature of relations" ( §6). Although their love for books compels them to treat books with respect, it does not, therefore, follow that books objectively deserve to be treated with respect -let alone mean that "books do in fact have moral status" (Ibid).…”
Section: Relationism and Moral Statusmentioning
confidence: 99%
See 1 more Smart Citation